A fairclough-based Analysis of Persuasive Strategies in Trump and Biden’s Speeches - Mustafa, Shaimaa (BELT - Brazilian English Language Teaching Journal, 2023)
This study investigates the inaugural speeches delivered by Trump and Biden in terms of Fairclough’s (1995) three-dimensional method of CDA. It highlights the link between micro and macro analysis of discourse by considering repetition, creativity, and intertextuality as the main persuasive strategies employed by both political leaders to make their audience believe in their ideas. The study also clarifies to what extent Trump and Biden vary in the use of these persuasive strategies in association with power distribution and ideological stands. The results show that Trump constructs a particular type of unity characterized by loyalty and allegiance through his use of pronouns and his thematization of ‘’people’’. By employing metaphors and negative expressions, Trump succeeds in painting a bleak, dark, and scary image of the United States as a country plagued by a rise in crime and a decay in the economy. Moreover, Trump does not venerate the past; rather he positions himself as only being limited by God by only borrowing texts associated with the bible. In contrast, Biden’s liberal ideology stands clear in offering a conception of unity that bands all people together as citizens of the nation by his frequent use of pronouns. He is very skilled at portraying an optimistic view of America’s future through his use of light metaphor and his positive rhetoric. Biden accentuates the idea that disagreement is part of democracy. However, disagreements should not lead to disunion. In addition, Biden tends to use more intertextuality in his speech than Trump. Biden’s ideology depends on accepting the other regardless of his political stands.